Planning and Evaluation of an Educational Program Based on PRECEDE Model to Improve Physical Activity in Female Students - F Estebsari; D Shojaeizadeh; D Mostafaei; M Farahbakhsh (Tehran University of Medical Sciences, 2010)
Background & Objective: Physical activity is one of the main components of lifestyle. Lack of physical activity along with unhealthy eating result in chronic diseases such as heart diseases, diabetes, and osteoporosis. This study aimed to design an educational program for improving physical activity in secondary school female students in Tonkabon in 2008.Methods & Materials: This study was an educational intervention in which 600 students enrolled in the study. The participants were allocated randomly in the intervention (n=300) and control (n=300) groups. Data were gathered using "International Physical Activity Questionnaire" and a standardized questionnaire -according to PRECEDE model- at baseline. The program was planned according to the PRECEDE model and was implemented in the intervention group students. Data were gathered two months after the intervention in both groups. Data were analyzed using Chi-Square, t-test, variance and regression analysis tests in the SPSS and STATA.Results: Following the educational intervention, the mean scores of the predisposing factors (knowledge and attitude), enabling factors, and reinforcing factors as well as the behavior were significantly increased in the intervention group compared to the control group (P<0.001).Conclusion: The findings showed that this structured program is useful in improving physical activity in female students.